Price Behavior under Alternative Forms of Price Expectations - Fishman, George S. (Quarterly Journal of Economics, 1964)
Introduction, 281. — Relatively perfect price knowledge, 285. — Equilibrium price expectation, 286. — The cobweb theorem, 289. — Adaptive expectations hypothesis, 291. — Rational expectations hypothesis, 294. — Conclusions and observations, 297.